The Effect of Virtual Reality Gaming on Developing Computational Thinking Skills - Sukirman, Sukirman; Ibharim, Laili Farhana Md; Said, Che Soh; Murtiyasa, Budi (The Indonesian Journal of Computer Science, 2024)
In the digital age, where programming prowess is increasingly crucial, the enhancement of Computational Thinking (CT) skills becomes essential. This study ventures into the scarcely explored domain of leveraging game-based learning (GBL) within virtual reality (VR) settings to bolster CT skills. Specifically, it introduces "CT Saber," a VR game inspired by the popular "Beat Saber," tailored to cultivate CT competencies. Employing a Design and Development Research (DDR) methodology across five stages—analysis, design, development, implementation, and evaluation—this investigation assessed the game's impact on 37 computer science students (25 male, 12 female) aged 21-24. A quasi-experimental design with pretest-posttest evaluation was utilized, revealing significant enhancements in CT skills post-intervention (Z = -4.496, p < 0.05), as analyzed through Wilcoxon Signed-Rank tests. The findings underscore the VR game's efficacy in CT skill development, suggesting a promising direction for integrating VR technologies in programming education.